Reason and Lovelessness : Essays, Encounters, Reviews 1980-2017. - Hill, Barry (Monash University Publishing, 2018)
Barry Hill is a multi-award winning writer of poetry, essays, biography, history, criticism, novels, short stories, libretti, and reportage. As a writer, Hill's voice is informed by his Australian working-class and militant union background, which has been distilled by his higher education in history and philosophy at the Universities of Melbourne and London. Hill's voice is unique, and his insight both profoundly important and capable of taking the reader to places not glimpsed before or imagined visible. His major works include Sitting In (1992), a landmark memoir in Labour History; Broken S.